Productivity of purebred Adal and quarterbred Saanen x Adal goats in Ethiopia - Awgichew, K.; Yacob, Y.; Fletcher, I. (1989)
The productivity of Ethiopian Adal and quarterbred Saanen x Adal goats was compared over 5 yr. Annual percentages of does kidding and of multiple births were 79 and 39. Kids born and kids weaned per doe joined were 1.12 and 0.95. Birth weights were 2.2 kg. Mortality rates from birth to weaning (3 mo), between 3 mos and 6 mos and between 6 mos and 12 mos were 14%, 6% and 4%. No differences (P > 0.05) between the genotypes were noted in any of the foregoing parameters. Quarterbred Saanen x Adal does produced more (P < 0.001) milk (31 kg) during a12 wk lactation than Adal does (24 kg). Progeny of the quarterbreds were heavier (P < 0.01) at 3 mo (9.7 kg) and at 6 mo (13.6 kg) than those of the Adal at the same ages (8.9 kg and 12.8 kg). Mature weight did not differ between the 2 genotypes (P > 0.05). Crossing Adal goats with Saanens to the quartebred level could increase milk production in the existing pastoral system without reducing other aspects of productivity and with no requirement for improved management or increased feed resources.